Caring for Health Professionals in the COVID-19 Pandemic Emergency: Toward an “Epidemic of Empathy” in Healthcare - Barello, Serena; Graffigna, Guendalina (Frontiers in Psychology, 2020)
Psychological research in healthcare opened the door to understanding people emotional reactions when experiencing events perceived as life-threatening. This is the case of the current outbreak of the novel Coronavirus disease (COVID-19) that has been recently declared “a public health emergency of international concern (PHEIC)” by the World Health Organization (WHO). The response to a pandemic influenza might generate remarkable stress and emotional turmoil to healthcare providers who work during the outbreak too. Prior experience with disasters, pandemics and major traumatic events indicates that enhanced support to healthcare professionals to become aware of their own emotions and effectively share their perspective and lived experience with patients can help them in remaining efficient and focused also during these stressful events. This outbreak marks a vital moment where healthcare systems can endorse an “epidemic of empathy” aimed at bringing science and humanism together to benefit patients and consolidate citizens’ trust in healthcare providers during this and future healthcare crisis. Perhaps, the greatest opportunity for managing people fears during health emergencies - like the COVID-19 one - in the short term - lies in restoring our connections with each other. Today, we are all called to rebuild a sense of community and the ties that engage us together as human beings.